The impact of climate change on policy‐relevant indicators of temperature extremes in the United Kingdom. Issue 2 (29th July 2021) - Arnell, Nigel W.; Freeman, Anna
Abstract: Climate change will increase the frequency of heatwaves in the United Kingdom and reduce the frequency of cold spells. This paper evaluates the effect of changes in climate as represented by UKCP18 climate projections on a series of indicators of heat and cold extremes relevant to policy in the United Kingdom. These indicators are expressed in terms of current critical thresholds beyond which alerts are issued or specific actions implemented, rather than impacts on health and well‐being. The frequency and duration of heatwave and heat–health alerts increase under all scenarios, with the greatest absolute number of events in the south and east of England where the chance of hot weather events affecting worker productivity doubles by the 2020s. Cold weather events – triggering health and social care plans and benefit payments – will become less frequent, but the effects of climate change on cold events are much smaller than on hot events and they will continue to occur. Until at least the 2040s, the projected effects of climate change do not depend strongly on the assumed change in global emissions, and the range in possible changes is primarily determined by uncertainty in the change in temperature in the United Kingdom for a given emissions pathway. Beyond the 2050s, the impacts are strongly dependent on future emissions. Impacts in a high‐emissions world will be considerably larger than in low‐emissions world. The projected increase in heatwave alerts, and the duration and intensity of heatwaves, implies not only a need to review heatwave emergency planning arrangements – looking in particular at what should become regarded as 'normal' summer weather – but also increased efforts to reduce vulnerability to extreme heat events. At the same time, cold weather events will still continue to occur with a sufficient frequency that plans need to be maintained.